Madrasah Vokasi (MA Kejuruan) Masih Minim Kolaborasi dengan Dunia Usaha dan Industri - Muhammad Affandi (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy paper elaborates that Madrasah Aliyah Kejuruan (MAK), as an integral part of Indonesia's vocational education system, faces significant challenges due to limited collaboration with the Business and Industry Sector. The lack of effective partnerships between MAK and industry results in a mismatch between the curriculum taught and the needs of the job market, which in turn affects the employability of MAK graduates in the industrial sector. The main causes of this issue include insufficient integrated planning, the absence of a dedicated team to manage relationships with industry, and limited human resource capacity involved in vocational education. Furthermore, inadequate communication and lack of evaluation mechanisms hinder the establishment of sustainable and effective partnerships. The methodology employed in this paper is literature study and policy analysis with a qualitative approach. Data were collected from various secondary sources including academic documents, government reports, and regulatory frameworks. The analysis was conducted using the USG (Urgency, Seriousness, Growth) framework to prioritize problems, fishbone diagram to identify root causes, and William N. Dunn's policy evaluation criteria to assess alternative solutions. This analytical approach enables systematic identification of problems and formulation of evidence-based policy recommendations. This paper analyzes these issues through theoretical approaches that include partnership management, network-based collaboration models, and resource-based theories. Proposed policy alternatives to enhance collaboration include the formulation of mandatory collaboration regulations between MAK and industry, strengthening partnership capacity through training and incentives, and integrating MAK into the national vocational system.